Formation of Tridymite and Evidence for a Hydrothermal History at Gale Crater, Mars. Issue 3 (10th March 2021) - Yen, A. S.; Morris, R. V.; Ming, D. W.; Schwenzer, S. P.; Sutter, B.; Vaniman, D. T.; Treiman, A. H.; Gellert, R.; Achilles, C. N.; Berger, J. A.; Blake, D. F.; Boyd, N. I.; et al.
Abstract: In August 2015, the Curiosity Mars rover discovered tridymite, a high‐temperature silica polymorph, in Gale crater. The existing model for its occurrence suggests erosion and detrital sedimentation from silicic volcanic rocks in the crater rim or central peak. The chemistry and mineralogy of the tridymite‐bearing rocks, however, are not consistent with silicic volcanic material. Using data from Curiosity, including chemical composition from the Alpha Particle X‐ray Spectrometer, mineralogy from the CheMin instrument, and evolved gas and isotopic analyses from the Sample Analysis at Mars instrument, we show that the tridymite‐bearing rocks exhibit similar chemical patterns with silica‐rich alteration halos which crosscut the stratigraphy. We infer that the tridymite formed in‐place through hydrothermal processes and show additional chemical and mineralogical results from Gale crater consistent with hydrothermal activity occurring after sediment deposition and lithification. Plain Language Summary: In August 2015, the Curiosity Mars rover discovered tridymite, an unexpected mineral phase, in Gale crater. The existing model for its occurrence suggests erosion and deposition from silicon‐rich volcanic rocks in the crater rim or central peak. The chemistry and mineralogy of the tridymite‐bearing rocks, however, are not consistent with silicon‐rich volcanic material. Using data from Curiosity's instrument suite, we show that the tridymite‐bearing rocks exhibit similar chemical patterns with silicon‐rich alteration zones which crosscut the layered sediments. We infer that the tridymite formed in‐place through hydrothermal processes and show additional chemical and mineralogical results from Gale crater consistent with hydrothermal activity occurring after sediment deposition and lithification. Key Points: Chemical and mineralogical data from the Curiosity Mars rover suggest a history of hydrothermal alteration within Gale crater Silica‐rich alteration halos and tridymite‐bearing deposits exhibit similar chemical signatures, suggesting related formation processes We propose the in situ formation of tridymite through hydrothermal processes as an alternative to a detrital origin